SOA-NOLM based and, XOR, parity generator and checker
All-optical systems are attractive in signal processing for digital logics due to its higher bandwidth than the conventional electronic based circuits. Researches have shown that photonic integrated circuits might replace the way data is handling in logical implementation. All-optical logic gates based on the integration of semiconductor optical amplifier and nonlinear optical loop mirror (SOA-NOLM) is one of the most compact design schemes in all-optical systems. The SOA is chosen as a nonlinear element since it has several nonlinearity effects such cross gain modulation (XGM), cross phase modulation (XPM), and four wave mixing (FWM). These effects can only be realized by having two signals propagating into the nonlinear medium such as the SOA. In this work, two optical sources at different wavelengths 1542 nm and 1555 nm are employed as data stream and gate switching respectively. The intensity of switching signal is set to be higher than data stream signal therefore only this signal is allowed to modify SOA optical properties by modulating the carrier density in the SOA. Thus the data stream signals will face gain nonlinearity if they enter into the SOA just after the modulation of the carrier densities by cross gain modulation (XGM) and cross phase modulation (XPM). Applying the XGM and XPM in the SOA-Nonlinear Loop Mirror configuration has caused the signal to be switched ON and OFF repeatedly. Generally, this study focuses on the characterization and application of the SOA-NOLM. Once the basic SOA-NOLM is designed, the semiconductor optical amplifier, SOA is characterized by a set of simulations in obtaining the optimum parameters for gates operation. Primitive gates such AND gate is designed then is simulated to ensure the produced signal meet the Boolean expression for the given input signals.